2020
DOI: 10.3390/ijerph17061867
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IAQ Management Using an IoT-Based Indoor Garden

Abstract: This study was designed to verify the effectiveness of smart gardens by improving indoor air quality (IAQ) through the installation of an indoor garden with sensor-based Internet-of-Things (IoT) technology that identifies pollutants such as particulate matter. In addition, the study aims to introduce indoor gardens for customized indoor air cleaning using the data and IoT technology. New apartments completed in 2016 were selected and divided into four households with indoor gardens installed and four household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Piasecki and Kostyrko [93] developed a method based on a decision matrix that includes six attributes: actual indoor air CO 2 concentration, TVOCs, and formaldehyde concentration, and their anthropogenic and construction product emissions to the indoor environment with a combined weighting scheme for an IAQ index equation. Kim et al [94] suggested an IAQ index which reflects PM 2.5 and CO 2 , divided into five grades from "good" to "hazardous" with a scale of 1 to 100 points, as follows: "good" (0-20); "moderate" (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); "unhealthy for a sensitive group" (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), "bad" (61-80), and "hazardous" (81)(82)(83)…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Piasecki and Kostyrko [93] developed a method based on a decision matrix that includes six attributes: actual indoor air CO 2 concentration, TVOCs, and formaldehyde concentration, and their anthropogenic and construction product emissions to the indoor environment with a combined weighting scheme for an IAQ index equation. Kim et al [94] suggested an IAQ index which reflects PM 2.5 and CO 2 , divided into five grades from "good" to "hazardous" with a scale of 1 to 100 points, as follows: "good" (0-20); "moderate" (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); "unhealthy for a sensitive group" (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), "bad" (61-80), and "hazardous" (81)(82)(83)…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…IoT-based indoor gardens: There has been extensive research to monitor IAQ through IoT and wireless sensors network (WSN) (Caquilpán P. et al , 2019; Kannaki et al , 2020; Pantazaras et al , 2018; Parkinson et al , 2019; Singla et al , 2018). However, a recent study has used smart gardens and IoT technology to clean and purify IAQ (Kim et al , 2020). In this study, the effectiveness of indoor gardens was measured and compared to buildings with no indoor gardens using smart technologies.…”
Section: Results: Qualitative Analysis Of Selected Publicationsmentioning
confidence: 99%
“…In this study, the effectiveness of indoor gardens was measured and compared to buildings with no indoor gardens using smart technologies. The results showed that the installation of an indoor garden reduced the amount of PM and CO 2 in the indoor environment (Kim et al , 2020).…”
Section: Results: Qualitative Analysis Of Selected Publicationsmentioning
confidence: 99%
“…The author accessed the required air exchange rates for mechanical and naturally ventilated schools in order to minimize the airborne spread of the virus ( Stabile et al, 2021 ). Management of IAQ using an IoT-based indoor garden was evaluated by Kim et al (2020) . An IoT-based IAQ monitoring system was used to collect real-time data on PM 2.5 , CO 2 , temperature, and humidity in the study.…”
Section: Indoor Air Quality Improvement Strategiesmentioning
confidence: 99%